Client Legal Protection in Psychological Services: An Analysis of Regulatory Frameworks, Ethical Norms, and Practical Challenges in Indonesia - Ridwan Rahmawan (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to critically examine the legal protection system for clients of psychological services in Indonesia, particularly in relation to violations of informed consent, data confidentiality, and malpractice. The research method uses a normative juridical approach, focusing on the analysis of relevant legislation, professional codes of ethics, and jurisprudence. This approach is supported by a literature review and qualitative analysis to compare the normative ideal (das Sollen) with empirical reality (das Sein). A comparative approach is also applied to identify gaps, overlaps, and weaknesses in regulations. The novelty of this research lies in its integration of health law, psychological ethics, and digital service regulations within a single analytical framework. Unlike previous studies that discussed these aspects separately, this study offers a holistic and systematic model to harmonize lex specialis regulations, strengthen ethical and legal enforcement, and institutionalize victim-centered accountability mechanisms in psychological services. The results of the study show that there is a significant imbalance between the protection afforded to victims of physical harm in medical malpractice and victims of psychological harm in psychological malpractice. While victims of medical malpractice can access civil or criminal legal remedies and receive compensation, clients of psychological services often face limited options, with most cases being resolved through administrative sanctions without material compensation. The conclusions of this study indicate that Indonesia must strengthen legal protections for clients of psychological services by harmonizing regulations, standardizing informed consent procedures, improving legal literacy, consistently enforcing ethical and legal obligations, and ensuring accessible complaint and compensation mechanisms. These steps are essential to protect clients' rights, promote justice, and improve accountability in the mental health care sector.